1998
DOI: 10.1017/s0022029997002847
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of Camelus dromedarius milk caseins

Abstract: αs1-, αs2-, β- and κ-caseins from Somali camels (Camelus dromedarius) were purified by acid precipitation at pH 4·4, crudely separated into an α-CN and a β-CN fraction and further purified by reversed-phase HPLC. Fragments of tryptic digests were sequenced. Amino acid patterns obtained were used to screen a cDNA library constructed from mRNA from lactating udder tissue. Full length clones corresponding to the four caseins were sequenced. The numbers of residues in the sequences deduced were αs1-CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
154
4
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(209 citation statements)
references
References 18 publications
22
154
4
1
Order By: Relevance
“…Surprisingly, the situation is quite the opposite in the case of equine caseins, about which even less is known than caseins from different Camelidae [2,9,17,20,22,24].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Surprisingly, the situation is quite the opposite in the case of equine caseins, about which even less is known than caseins from different Camelidae [2,9,17,20,22,24].…”
Section: Introductionmentioning
confidence: 90%
“…* Les données concernant les caséines de vache, chèvre, souris et porc sont issues de la base de données Swissprot ; ¦ selon Ochirkhuyag et al [24] ; § selon Kappeler et al [17].…”
Section: Thermally Precipitated Casein Subfractionsunclassified
See 1 more Smart Citation
“…Hypoallergenicity of mothers' milk was reported to be due to the high percentage of b-CN, low percentage of a-CN [28], deficiency of b-lactoglobulin [54] and similarity of the immunoglobulins [105]. It has been reported that camel milk could be a new protein source for children allergic to bovine milk.…”
Section: Camel Milk Safe For People Allergic To Bovine Milkmentioning
confidence: 99%
“…CM's lactoferrin has very high levels of bactericidal and bacteriostatic properties against Gram-positive and Gram-negative bacteria (19), more than cow and human lactoferrin. CM contains various protective proteins, mainly enzymes which exert antibacterial and immunological properties (20). The fact that CM lacks β-lactoglobulin and a "new" β-casein (21), two powerful allergens in cow milk, makes the milk attractive for children suffering from milk allergies (22).…”
mentioning
confidence: 99%